2014
DOI: 10.1021/jp507520c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Excitonic Coupling and Charge-Transfer States in the Absorption and CD Spectra of Adenine-Based Oligonucleotides Investigated through QM/MM Simulations

Abstract: In this work, we study the photophysical properties of an adenine-based oligonucleotide using an ensemble of about 200 configurations obtained from molecular dynamics simulations. Specifically, a QM/MM approach is used to obtain the excited-state energies and properties of (dA)20(dT)20 with a dimer of π-stacked adenine bases included in the quantum region. The absorption and circular dichroism spectra are computed and analyzed using the algebraic diagrammatic construction through second order level of theory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 87 publications
(196 reference statements)
9
74
0
Order By: Relevance
“…Properties of Franck-Condon excited states of NAs have been a subject of extensive quantum mechanical (QM) studies with the use of ab initio methods and timedependent density functional theory (TD DFT) [11][12][13][14][15][16][17][18][19][20] . NA stacked dimers, as a main model system in the high level ab initio calculations of vertical transitions, exhibit no markedly red-shifted transitions compared to monomer absorption, apart from a small ~ 0.1 eV exciton splitting in homodimers 11-13 , resulting in a weak wavelength tail 11 relative to the monomer's spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Properties of Franck-Condon excited states of NAs have been a subject of extensive quantum mechanical (QM) studies with the use of ab initio methods and timedependent density functional theory (TD DFT) [11][12][13][14][15][16][17][18][19][20] . NA stacked dimers, as a main model system in the high level ab initio calculations of vertical transitions, exhibit no markedly red-shifted transitions compared to monomer absorption, apart from a small ~ 0.1 eV exciton splitting in homodimers 11-13 , resulting in a weak wavelength tail 11 relative to the monomer's spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results also show that nearest base-base interactions can indeed satisfactory describe absorption 21 and circular dichroism spectra 22 . It has also been shown that only delocalized excitonic ππ* states contribute to the low-energy part of the absorption spectra, while charge-transfer (CT) transitions appear to be blue-shifted relative to absorption maximum 11,12,[15][16][17][18] . Meantime, a significant deviation of the fluorescence excitation spectra of some dinucleotides and oligonucleotides from their absorption spectra in the 290-310 nm region 21,23,24 , a long-wavelength tail in DNA absorption spectra 25,26 suggested possible electronic transitions in that spectral range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…well above the L a and L b bands (Fig. 2) 32 . They are found to mix with the energetically close lying bright B a and B b bands borrowing partially their oscillator strength.…”
Section: Mechanistic Picture and De-excitation Pathwaysmentioning
confidence: 90%
“…Although this mechanism is not supported by QM/MM computations 31,32,58 , other groups have considered the possibility to populate low lying CT states directly in the FC region 8,64 . In this regard we would like to draw attention to a recent paper by Rohlfing and co-workers which argues that aqueous solvation may lower CT states by more than 1 eV based on many-body Green's function computations 64 .…”
Section: -18mentioning
confidence: 99%